Development of PjBL-Based Digital Curriculumtoimprove Critical Thinking Skillsin Grade IV Science subjects SDN 18 Dodu Bima City - Juwita Anggini (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This research aims todevelop a Project-Based digital module (PjBL) toimprove the critical thinking skills of fourth grade students learningsocial studies at SDN 18 Dodu, Bima City. The Borg & Gall model of Research & Development methods is limited to sixstages: needs analysis, product design, development, expert validation, limited trials, and effectiveness tests. The module is presente dasan interactive flipbook (Canva + Heyzine). The instrumentsare in the form of validation sheets, questionnaires, and pre- and post-test tests. Media experts (score 92%) and subject matter experts (90%) rated the modules "very worthwhile". A practicality test on 10 studentsshowed a "very good" response (88%). Effectiveness testing on 17 studentsobtained an N-Gain of 0.61 (moderate-effective category) which indicatesa significantimprovement in critical thinkingskills. Thus, the PJBL-based digital modules developed are valid, practical, and effectivetoimprovecriticalthinkingskillsin science learning.